Legal Analysis of Criminal Responsibility of Gambling Crime Perpetrators (Study of Decision Number 234/Pid.B/2024/PN Jkt Pst) - Darmawan, Kurnia Sobar; Sugiharto, Sugiharto (Jurnal Hukum Khaira Ummah, 2025)
Gambling is a game where players bet to choose one of several choices provided where only one choice is the winner. This action is clearly contrary to the provisions of positive law, religion, and morality which is very dangerous for the next generation. The crime of gambling or participating in gambling was originally prohibited in the criminal provisions of Article 542 of the Criminal Code, but based on the provisions stipulated in Article 2 paragraph (4) of Law No. 7 of 1974 concerning the regulation of gambling, its name has been changed to a crime regulated in Article 303 bis of the Criminal Code. The approach method used in this study is a normative legal approach. The normative legal approach is a legal research conducted by examining library materials or secondary data as only. The research specifications used are descriptive analysis, sources and types of data used are primary and secondary data. The data collection method is carried out by means of literature studies, including minutes of legislation, books, journals, research results. The problem is analyzed with the theory of criminal responsibility, the theory of legal certainty and the theory of justice. Criminal liability is liability for crimes committed by people. Based on Decision Number 234/Pid.B/2024/PN Jkt Pst which is based on the facts revealed in the trial that the criminal act of gambling was committed by the Defendants by referring to the evidence revealed in the trial, it can be concluded that the Defendants have been proven guilty of the crime of gambling. This action expressly violates Article 303 paragraph 1 of the Criminal Code, with all the elements contained therein fulfilled. The basis for the judge's considerations in making a decision can be divided into two categories, namely: Legal considerations, namely the judge's considerations based on legal facts revealed in the trial and by law specified as something that must be included in the decision, and non-legal considerations, namely the judge in making his decision looks more at the background of the defendant, the consequences of the defendant's actions and the defendant's personal condition and religion.